Inflammatory myofibroblastic tumour in the nasal cavity of a dog. (9th October 2013) - Swinbourne, F.; Kulendra, E.; Smith, K.; Leo, C.; Ter Haar, G.
<x xml:space="preserve">Abstract</x> A 4·5‐year‐old, female neutered Leonberger was presented with a 2‐month history of sneezing, nasal discharge and epistaxis. A presumptive diagnosis of nasal aspergillosis was made based on a suspected (fungal) granuloma on rhinoscopic examination and fungal hyphae on cytological examination. A poor response to targeted therapy was observed and computed tomography 16 months after initial presentation revealed a progressive, locally invasive mass lesion. Histopathological and immunohistochemical analysis of deep surgical biopsies revealed a spindle cell population and a plasma cell rich inflammatory infiltrate, with diffuse expression of vimentin, supporting a diagnosis of inflammatory myofibroblastic tumour. Complete resolution of the nasal discharge and reduced sneezing frequency was reported 9 months post‐surgical debridement via rhinotomy. To the authors' knowledge, this is the first report of IMT in the nasal cavity of a dog. IMT should be considered when presented with a nasal mass lesion, particularly if histopathological features and clinical course are inconsistent.